Improved Performance of Anti-miRNA Oligonucleotides Using a Novel Non-Nucleotide Modifier - Kim A Lennox; Richard Owczarzy; Derek M Thomas; Joseph A Walder; Mark A Behlke (Elsevier, 2013)
Anti-microRNA oligonucleotides (AMOs) are steric blocking antisense reagents that inhibit microRNA (miRNA) function by hybridizing and repressing the activity of a mature miRNA. First generation AMOs employed 2'-O-Methyl RNA nucleotides (2'OMe) with phosphorothioate (PS) internucleotide linkages positioned at both ends to block exonuclease attack. Second generation AMOs improved potency through the use of chemical modifications that increase binding affinity to the target, such as locked nucleic acid (LNA) residues. However, this strategy can reduce specificity as high binding affinity compounds can bind to and suppress function of related sequences even if one or more mismatches are present. Further, unnatural modified nucleic acid residues can have toxic side effects. In the present study, a variety of non-nucleotide modifiers were screened for utility in steric blocking antisense applications. A novel compound, N,N-diethyl-4-(4-nitronaphthalen-1-ylazo)-phenylamine ("ZEN"), was discovered that increased binding affinity and blocked exonuclease degradation when placed at or near each end of a single-stranded oligonucleotide. This new modification was combined with the 2'OMe RNA backbone to make ZEN-AMOs. The new ZEN-AMOs have high potency and can effectively inhibit miRNA function in vitro at low nanomolar concentrations, show high specificity, and have low toxicity in cell culture.